2014
DOI: 10.1016/j.juro.2013.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Adherence to Antimuscarinic Therapy in Everyday Practice: A Systematic Review

Abstract: Improvement in adherence and persistence with antimuscarinic medication should be an important goal in the development of new drugs for overactive bladder and urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 18 publications
4
117
0
Order By: Relevance
“…Younger age as a risk factor for discontinuation has also been reported elsewhere, 11,12 though this may be a confounder as younger patients generally tend to take fewer prescription medications.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Younger age as a risk factor for discontinuation has also been reported elsewhere, 11,12 though this may be a confounder as younger patients generally tend to take fewer prescription medications.…”
Section: Discussionmentioning
confidence: 62%
“…6 The principal drugs used for OAB are antimuscarinic agents. Unfortunately there is a high rate of discontinuation from these drugs, [7][8][9][10][11][12][13] with up to 86% of patients in a UK study stopping therapy after 1 year. 12 In a Canadian study of 31 754 patients with OAB who were treated with antimuscarinics, about 91% discontinued within a 4-year follow-up, and most did not have second-line treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, the compliance rate to treatment rate was found to range between 12.0 and 39.4 percent. [16] The most common reasons for withdrawal were side effects, and insufficient efficacy. However, in the current survey, approximately three fourths of all participants reported higher incidence of the side effects as the most important reason.…”
Section: Discussionmentioning
confidence: 99%
“…6 A systematic review of 14 studies of people with OAB found median persistence rates with antimuscarinic drugs ranged between 12% and 39% at 12 months, falling to between 6% and 12% at 24 months. 7 Rates of non-adherence and discontinuation of treatment for OAB are reportedly the same for men and women. 8 …”
Section: Adherence In Urologymentioning
confidence: 96%